Anisotropic Magnetized Cloud String Universe with Hybrid Expansion Law - Ramprasad, T.; Kiran, M.; Rao, M.P.V.V. Bhaskara (Discontinuity, Nonlinearity, and Complexity, 2026)
Anisotropic Bianchi type-III metric is studied with cloud strings and electromagnetic field in General Relativity. To get determinate solutions of field equations we have taken the help of (i) shear scalar proportional to scalar expansion proposed by Collins [1] and (ii) Hybrid expansion law proposed by Akarsu et al. [2]. We have obtained all the cosmological parameters corresponding to the model, also we have provided a physical discussion of our model using a graphical representation of these parameters. The physical and kinematical properties found in this model exhibit an accelerating expansion of the universe, which are compatible with current cosmological observations.